Critical structural and functional roles for the N-terminal insertion sequence in surfactant protein B analogs. - Frans J Walther; Alan J Waring; Jose M Hernandez-Juviel; Larry M Gordon; Zhengdong Wang; Chun-Ling Jung; Piotr Ruchala; Andrew P Clark; Wesley M Smith; Shantanu Sharma; Robert H Notter (PLoS ONE)
Background Surfactant protein B (SP-B; 79 residues) belongs to the saposin protein superfamily, and plays functional roles in lung surfactant. The disulfide cross-linked, N- and C-terminal domains of SP-B have been theoretically predicted to fold as charged, amphipathic helices, suggesting their participation in surfactant activities. Earlier structural studies with Mini-B, a disulfide-linked construct based on the N- and C-terminal regions of SP-B (i.e., approximately residues 8-25 and 63-78), confirmed that these neighboring domains are helical; moreover, Mini-B retains critical in vitro and in vivo surfactant functions of the native protein. Here, we perform similar analyses on a Super Mini-B construct that has native SP-B residues (1-7) attached to the N-terminus of Mini-B, to test whether the N-terminal sequence is also involved in surfactant activity. Methodology/results FTIR spectra of Mini-B and Super Mini-B in either lipids or lipid-mimics indicated that these peptides share similar conformations, with primary alpha-helix and secondary beta-sheet and loop-turns. Gel electrophoresis demonstrated that Super Mini-B was dimeric in SDS detergent-polyacrylamide, while Mini-B was monomeric. Surface plasmon resonance (SPR), predictive aggregation algorithms, and molecular dynamics (MD) and docking simulations further suggested a preliminary model for dimeric Super Mini-B, in which monomers self-associate to form a dimer peptide with a "saposin-like" fold. Similar to native SP-B, both Mini-B and Super Mini-B exhibit in vitro activity with spread films showing near-zero minimum surface tension during cycling using captive bubble surfactometry. In vivo, Super Mini-B demonstrates oxygenation and dynamic compliance that are greater than Mini-B and compare favorably to full-length SP-B. Conclusion Super Mini-B shows enhanced surfactant activity, probably due to the self-assembly of monomer peptide into dimer Super Mini-B that mimics the functions and putative structure of native SP-B.